Language program evaluation theory and practice - Lynch, Brian K. (Cambridge University Press, 1996)
Although much has been written about the testing and evaluation of language students, few books have dealt with the much broader issue of measuring the success of language programs. Filling a critical gap in the literature of applied linguistics, Language Program Evaluation provides teachers, researchers, and administrators with a complete introduction to both qualitative and quantitative approaches to evaluating the effectiveness of their programs. Through a careful blend of theory, research, and practice, the author presents a testing model that is specifically tailored to the concerns of language education programs and which can be adapted to different contexts and updated as teaching and learning situations evolve. He proposes a shift from purely quantitative studies which consider only end-of-program achievement gains to ones that include an investigation of program process using qualitative, naturalistic methods
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Sprache; Language and languages / Study and teaching / Evaluation; Sprachkurs; Computerlinguistik; Evaluation